The teaching of English as a foreign language at The National University Of Malaysia: some maters of relevance. - Dahnil Adnani (Universiti Kebangsaan Malaysia, 1975)
This article attempts to describe the various problems encountered in the development of the program of Teaching of English as s Foreign Language (TEFL) at the National University of Malaysia and the various attempts made at dealing with these problems. It also attempts to identify certain areas that need to be given serious attention in the subsequent development of the program, such as: